Pengaruh Kepercayaan Terhadap Keputusan Berkunjung Melalui Kepuasan Pada Danau Situ Gintung, Ciputat, Tangerang Selatan, Provinsi Banten - Tarigan, Emenina; Suprina, Rina; Leonandri, Dino Gustaf; Pramanik, Purwanti Dyah; Dewi, Triana Rosalina (Jurnal Ilmiah Pariwisata, 2025)
This study aims to analyze the influence of trust on visit decisions through visitor satisfaction at the tourist destination of Danau Situ Gintung, Ciputat, South Tangerang. The research employed a quantitative method using Structural Equation Modeling (SEM) with SmartPLS. Data were collected from 150 visitors selected through purposive sampling. The results indicate that trust significantly affects both visitor satisfaction and visit decision. Furthermore, satisfaction mediates the relationship between trust and visit decision significantly. These findings emphasize the importance of building visitor trust by providing credible information, professional services, and safe facilities to enhance satisfaction and encourage revisit intentions. This study offers theoretical contributions to the understanding of tourist behavior and practical implications for destination managers in improving service quality and promotional strategies. Keywords: trust, visitor satisfaction, visit decision